Pharmacokinetics, pharmacodynamics, and safety of prandial oral insulin (N11005) in healthy subjects - Pan, Qi; Wang, Xiaoxia; Li, Wenjia; Chen, Xiaofeng; Zhuang, Yulei; Zhou, Qinghong; Huang, Yuhui; Zhou, Yijie; Lan, Li; Wang, Zhijie; Wang, Wenjia; Hong, Juan; et al. (Frontiers in Endocrinology, 2023)
Aims: To verify whether the oral insulin N11005 is administered as a prandial insulin by assessing the pharmacokinetics (PK), pharmacodynamics (PD) and safety profiles of N11005 with a short-acting biosynthetic human insulin (Novolin R) as reference.Methods: This was a randomized, open-label, single-dose, crossover hyperinsulinemic-euglycemic clamp study in healthy Chinese male subjects. A total of 12 subjects were enrolled in the test (T) group (N11005, 300 IU, p.o.) and the reference (R) group (Novolin R, 0.1 IU/Kg, i.h.) with a washout period of 14 days. All subjects were administered on the same day of the clamp study. Glucose Infusion Rates (GIR), serum insulin and C-peptide concentration were determined during every 8-hour clamp cycle. Trial registration: Clinicaltrials.gov identifier NCT04975022.Results: After administration, the ratios of mean serum C-peptide concentration to baseline concentration in both T and R groups were lower than 50%, which confirmed the stability of the clamp platform. T group (N11005) showed a more rapid onset of action (tGIR10%max≈11 min) and a comparable duration of action to R group, which was basically in line with the characteristics of prandial insulins. No adverse events (AEs) occurred throughout the study, which demonstrated that N11005 and Novolin R are safe and well-tolerated.The PD profiles of the single-dose N11005 in human body are similar to those of prandial insulins, with an excellent safety profile.